Early Medication Nonadherence After Acute Myocardial Infarction. (July 2015) - Mathews, Robin; Peterson, Eric D.; Honeycutt, Emily; Chin, Chee Tang; Effron, Mark B.; Zettler, Marjorie; Fonarow, Gregg C.; Henry, Timothy D.; Wang, Tracy Y.
<x xml:space="preserve">Abstract</x> Background— Nonadherence to prescribed evidence-based medications after acute myocardial infarction (MI) can contribute to worse outcomes and higher costs. We sought to better understand the modifiable factors contributing to early nonadherence of evidence-based medications after acute MI. Methods and Results— We assessed 7425 acute MI patients treated with percutaneous coronary intervention at 216 US hospitals participating in TReatment with ADP receptor iNhibitorS: Longitudinal Assessment of Treatment Patterns and Events after Acute Coronary Syndrome (TRANSLATE-ACS) between April 2010 and May 2012. Using the validated Morisky instrument to assess cardiovascular medication adherence at 6 weeks post MI, we stratified patients into self-reported high (score, 8), moderate (score, 6–7), and low (score, <6) adherence groups. Moderate and low adherence was reported in 25% and 4% of patients, respectively. One third of low adherence patients described missing doses of antiplatelet therapy at least twice a week after percutaneous coronary intervention. Signs of depression and patient-reported financial hardship because of medication expenses were independently associated with a higher likelihood of medication nonadherence. Patients were more likely to be adherent at 6 weeks if they had follow-up appointments made before discharge and had a provider explain potential side effects of their medications. Lower medication adherence may be associated with a higher risk of 3-month death/readmission (adjusted hazard ratio, 1.35; 95% confidence interval, 0.98–1.87) although this did not reach statistical significance. Conclusions— Even early after MI, a substantial proportion of patients report suboptimal adherence to prescribed medications. Tailored patient education and pre discharge planning may represent actionable opportunities to optimize patient adherence and clinical outcomes. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01088503.